Crack Recognition Algorithm Integrating Attention Mechanism and Region Growth Method - LING Xiaokang; ZHAN Jie; MA Jianfei (Renmin Zhujiang)
To optimize traditional crack identification methods,improve the robustness and accuracy of the crack identification method,and realize automatic crack identification,this paper proposes a crack recognition algorithm integrating attention mechanism and region growth.It establishes dynamic thresholds and obtains the crack results under different thresholds by employing the region growth method.The attention mechanism is introduced to assign different weight coefficients to each pixel of the image according to the crack identification under dynamic thresholds for more accurate crack recognition results.Finally,the characteristic information of cracks is determined by the length of the crack skeleton and the area occupied by the crack region (length and average width of the crack).Through verifying field crack images,the results show that the crack characteristic information identified by the crack identification method integrating attention mechanism and region growth is basically consistent with the actual crack characteristics.The method features strong robustness and identification accuracy,which provides support for engineering health monitoring.